Determining the nutritional values of new corn varieties on pigs and broilers - Cao, Hongrui; Yan, Lei; Song, Xiaoming; Liu, Ling; Xu, Shaohua; Hu, Shengdi; Zhang, Shuai (Frontiers in Veterinary Science, 2024)
The objective of this study was to evaluate the nutritional values of three new corn varieties (high-iron corn, cadmium-resistant corn, low-phytate phosphorus corn) cultivated with molecular marker-assisted selection breeding technique fed to growing pigs and broilers. Exp. 1 was conducted to compare the nutritional values of high-iron corn, high-chromium corn, low-phytate phosphorus corn and conventional corn fed to growing pigs based on a 15×2 Youden square design. Exp.2 was conducted to compare the nutritional values of high-iron corn, low-phytate phosphorus corn and conventional corn fed to broilers based on a completely randomized design. Parameters including nutrient digestibility, available energy and amino acids, and mineral deposition were measured. The results shows that the iron content in the high-iron corn and the cadmium content in the cadmium-resistant corn were 29.608 mg/kg and 0.0057 mg/kg, respectively, both were greater than those in the other three kinds of corns. When fed to growing pigs, the neutral detergent fiber digestibility of the high-iron corn group was lower than that of the conventional corn group (P < 0.05), and the acid detergent fiber digestibility of the high-iron group and the low-phytate phosphorus corn group was lower than that of the conventional corn group (P < 0.01). In addition, the digestible energy value of the high-iron corn in growing pigs was lower than that of the conventional corn (P < 0.05). When fed to broilers, it was observed that the tibia length of the low-phytate phosphorus corn group and the high-iron corn group